(NAS Colloquium) Elliptic Curves and Modular Forms (The National Academies Press, 1998)
Keywords: Biology and Life Sciences; Math, Chemistry, and Physics; Surveys and Statistics

From Research to Reward: How a Political Scientist Knows What Our Enemies Will Do (Often Before They Do) - National Academy of Sciences (The National Academies Press, 2016)
Keywords: Explore Science; Policy for Science and Technology; Math, Chemistry, and Physics; Conflict and Security Issues; Surveys and Statistics

In the Light of Evolution: Volume VII: The Human Mental Machinery - National Academy of Sciences (The National Academies Press, 2014)
Humans possess certain unique mental traits. Self-reflection, as well as ethic and aesthetic values, is among them, constituting an essential part of what we call the human condition. The human mental machinery led our species to have a self-awareness but, at the same time, a sense of justice, willing to punish unfair actions even if the consequences of such outrages harm our own interests. Also, we appreciate searching for novelties, listening to music, viewing beautiful pictures, or living in well-designed houses. But why is this so? What is the meaning of our tendency, among other particularities, to defend and share values, to evaluate the rectitude of our actions and the beauty of our surroundings? What brain mechanisms correlate with the human capacity to maintain inner speech, or to carry out judgments of value? To what extent are they different from other primates' equivalent behaviors? In the Light of Evolution Volume VII aims to survey what has been learned about the human "mental machinery." This book is a collection of colloquium papers from the Arthur M. Sackler Colloquium "The Human Mental Machinery," which was sponsored by the National Academy of Sciences on January 11-12, 2013. The colloquium brought together leading scientists who have worked on brain and mental traits. Their 16 contributions focus the objective of better understanding human brain processes, their evolution, and their eventual shared mechanisms with other animals. The articles are grouped into three primary sections: current study of the mind-brain relationships; the primate evolutionary continuity; and the human difference: from ethics to aesthetics. This book offers fresh perspectives coming from interdisciplinary approaches that open new research fields and constitute the state of the art in some important aspects of the mind-brain relationships.
Keywords: Biology and Life Sciences

Report of the Treasurer for the Year Ended December 31, 2015 - National Academy of Sciences (The National Academies Press, 2016)
The income that supports the activities of the National Academy of Sciences (NAS) comes from two major sources: program revenue received from sponsors to pay for the myriad studies and other activities undertaken each year by the National Academies of Sciences, Engineering, and Medicine, and a much smaller sum that is obtained from our endowment under the endowment spending policies adopted by the Council. The goal of the endowment is to provide stable support for the Academy's programs and activities. To achieve this goal, the Council, acting on the recommendations of the Finance Committee, has historically authorized spending from the portfolio at a rate designed to maintain the purchasing power of the endowment over time. This Report of the Treasure of the National Academy of Sciences presents the financial position and results of operations as well as a review of the endowment, trust, and other long-term investments portfolio activities of our Academy for the year ended December 31, 2015. While this book provides essential financial summary to key personnel, it also serves as a vital informative resource for various members of the public, private, and governmental sectors.
Keywords: Policy for Science and Technology

India-United States Cooperation on Science and Technology for Countering Terrorism: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2014)
India and the United States are the world's two largest democracies with distinguished scientific traditions and experts in a wide range of scientific-technical fields. Given these strengths and the ability to learn from one another, the U.S. National Academy of Sciences together with the National Institute for Advanced Studies in Bangalore, India, held a joint Indian-U.S. workshop to identify and examine potential areas for substantive scientific and technical cooperation that can support counterterrorism efforts through the Homeland Security Dialogue and through direct cooperation. India-United States Cooperation on Science and Technology for Countering Terrorism is the summary of that workshop. This report examines topics such as biological threats; protection of nuclear facilities; security (physical and cyber) for chemicals, chemical facilities and other critical infrastructure; and monitoring, surveillance, and emergency response. The report also identifies and examines promising areas for further Indian-U.S. cooperation.
Keywords: Conflict and Security Issues

A History of the First Half-Century of the National Academy of Sciences: 1863-1913 (The National Academies Press, 1913)
The National Academy of Sciences is the third oldest American institution, being established after the Smithsonian Institute and the American Association for the Promotion of Science. The Academy dates back to 1863, right in the midst of the American Civil War. Fortunately for the time, the Academy was vital to the development of the war in favor of the Union through its establishment of much needed scientific advancements and insight tantamount to those of the academies in Great Britain and the rest of Europe despite the involvement of science's most primary men. Since then, the Academy has served as a scientific adviser to the government, an adviser greatly appreciated by the government. The Academy's recommendations have been adopted, its findings accepted, and its investigations used to better advance the nation as a whole. A History of the First Half-Century of the National Academy of Sciences: 1863-1913 (1913) illustrates the Academy's history from its creation to the appointment of Woodrow Wilson as president. The book features a detailed look into the founding and forming of the Academy; the annals of the academy including the classifications of membership in 1892; lists of those involved with the Academy including officers and foreign associates; the Academy's publications, and more.
Keywords: Policy for Science and Technology; Explore Science

Biotechnology in China - National Academy of Sciences (The National Academies Press, 1989)
Keywords: Biology and Life Sciences

The Mathematical Sciences: A Report - National Research Council (The National Academies Press, 1968)
Keywords: Math, Chemistry, and Physics; Policy for Science and Technology; Surveys and Statistics

The Life Sciences: Recent Progress and Application to Human Affairs The World of Biological Research Requirements for the Future (The National Academies Press, 1970)
Keywords: Health and Medicine

China Bound, Revised: A Guide to Academic Life and Work in the PRC - National Academy of Sciences (The National Academies Press, 1994)
Being prepared in China, says one researcher, can mean "the difference between a headache and a productive day." Acclaimed by readers, this friendly and practical volume—now updated with important new information—offers all the details academic visitors need to make long-term stays in China productive, comfortable, and fun. Academic opportunities have been revived in the years since the Tiananmen Square event, and the book opens with an overview of what we have learned from our academic exchanges with China, the opportunities now available, and resources for more information. To help visitors prepare for daily life, the book covers everything from how to obtain the correct travel documents to what kinds of snack foods are available in China, from securing accommodations to having the proper gift for your Chinese dinner host. Frank discussions on the research and academic environments in China will help students, investigators, and teachers from their initial assignment to a danwei, or work unit, to leaving the country with research materials intact. The book offers practical guidelines on working with Chinese academic institutions and research assistants, arranging work-related travel, managing working relationships, resolving language issues, and—perhaps most important—understanding Chinese attitudes and customs toward study, research, and work life. New material in this edition includes an expanded section on science and social science field work, with a discussion of computers: which ones work best in China, how to arrange to bring your computer in, where to find parts and supplies, how to obtain repairs, and more. Living costs, health issues, and addresses and fax numbers for important services are updated. Guidance is offered on currency, transportation, communications, bringing children into China, and other issues. Based on the first-hand reports of hundreds of academic visitors to China and original research by the authors, this book will be useful to anyone planning to live and work in China: students, researchers, and teachers and their visiting family members, as well as business professionals.
Keywords: Education

Biographical Memoirs: Volume 61 - National Academy of Sciences (The National Academies Press, 1992)
Biographic Memoirs: Volume 61 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Science and Human Rights (The National Academies Press, 1988)
Why does the National Academy of Sciences have a Committee on Human Rights? How does the committee define human rights and which rights are fundamental? Does a focus on human rights undermine efforts toward international scientific cooperation , development, political stability, or nuclear disarmament? Why does the committee work only in behalf of scientists and how do scientists become victims of human rights violations? How and why do some health professionals collude with torturers? These questions are typical of those asked frequently of the members and staff of the academy's Committee on Human Rights. They are important questions that this document helps to answer. Science and Human Rights is the summary of the presentation and discussion of a Symposium convened by the National Academy of Sciences to discuss these issues. Also included in this report are three major papers written by former prisoners from Chile, South Africa, and the Soviet Union.
Keywords: Behavioral and Social Sciences

Chemical Ecology: The Chemistry of Biotic Interaction - Eisner, Thomas; Meinwald, Jerrold (The National Academies Press, 1995)
Chemical signals among organisms form "a vast communicative interplay, fundamental to the fabric of life," in the words of one expert. Chemical ecology is the the discipline that seeks to understand these interactions-to use biology in the search for new substances of potential benefit to humankind. This book highlights selected research areas of medicinal and agricultural importance. Leading experts review the chemistry of:
Keywords: Math, Chemistry, and Physics; Biology and Life Sciences

(NAS Colloquium) Carbon Dioxide and Climate Change (The National Academies Press, 1997)
Keywords: Environment and Environmental Studies; Earth Sciences

(NAS Colloquium) Geology, Mineralogy, and Human Welfare (The National Academies Press, 1999)
Keywords: Earth Sciences; Environment and Environmental Studies

Biographical Memoirs: Volume 86 - National Academy of Sciences (The National Academies Press, 2005)
Biographic Memoirs Volume 86 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

In the Light of Evolution: Volume II: Biodiversity and Extinction - National Academy of Sciences (The National Academies Press, 2008)
The current extinction crisis is of human making, and any favorable resolution of that biodiversity crisis—among the most dire in the 4-billion-year history of Earth—will have to be initiated by mankind. Little time remains for the public, corporations, and governments to awaken to the magnitude of what is at stake. This book aims to assist that critical educational mission, synthesizing recent scientific information and ideas about threats to biodiversity in the past, present, and projected future. This is the second volume from the In the Light of Evolution series, based on a series of Arthur M. Sackler colloquia, and designed to promote the evolutionary sciences. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. Individually and collectively, the ILE series aims to interpret phenomena in various areas of biology through the lens of evolution, address some of the most intellectually engaging as well as pragmatically important societal issues of our times, and foster a greater appreciation of evolutionary biology as a consolidating foundation for the life sciences.
Keywords: Biology and Life Sciences

One Earth, One Future: Our Changing Global Environment - National Academy of Sciences (The National Academies Press, 1990)
Written for nonscientists, One Earth, One Future can help individuals understand the basic science behind changes in the global environment and the resulting policy implications that the population of the entire planet must face. The volume describes the earth as a unified system—exploring the interactions between the atmosphere, land, and water and the snowballing impact that human activity is having on the system—and presents perspectives on policies and programs that can both develop and protect our natural resources. One Earth, One Future discusses why such seemingly diverse issues as historical climate change, species diversity, and sea-level rise are part of a single picture—and how human activity is the critical element in that picture. The book concludes with practical examinations of economic, security, and development questions, with a view toward achieving improvements in quality of life without further environmental degradation. One Earth, One Future is must reading for anyone interested in the interrelationship of environmental matters and public policy issues.
Keywords: Earth Sciences; Environment and Environmental Studies

Addressing the Physician Shortage in Occupational and Environmental Medicine: Report of a Study (The National Academies Press, 1991)
Keywords: Health and Medicine

Japanese Investment and Technology Transfer: Report of a Workshop (The National Academies Press, 1992)
Keywords: Industry and Labor